The integrals in Gradshteyn and Ryzhik. Part 11: The incomplete beta function - Boyadzhiev, Khristo N.; Medina, Luis A; Moll, Victor H. (Scientia Series A: Mathematical Sciences, 2025)
The table of Gradshteyn and Rhyzik contains some integrals that can be expressed in terms of the incomplete beta function. We describe some elementary properties of this function and use them to check some formulas in the mentioned table.
Keywords: Integrals; Incomplete beta function; digamma function